2008
DOI: 10.1371/journal.pcbi.1000254
|View full text |Cite
|
Sign up to set email alerts
|

Game Theory of Mind

Abstract: This paper introduces a model of ‘theory of mind’, namely, how we represent the intentions and goals of others to optimise our mutual interactions. We draw on ideas from optimum control and game theory to provide a ‘game theory of mind’. First, we consider the representations of goals in terms of value functions that are prescribed by utility or rewards. Critically, the joint value functions and ensuing behaviour are optimised recursively, under the assumption that I represent your value function, your represe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
296
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 251 publications
(301 citation statements)
references
References 39 publications
3
296
1
1
Order By: Relevance
“…Instead, we must rely on our best estimates of others' beliefs and preferences to guide social decision making (21,43) and tread carefully when their fate rests in our hands. Here, we provide evidence for an apparently hyperaltruistic valuation of others' pain that is associated with slower choices when making decisions that affect others.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, we must rely on our best estimates of others' beliefs and preferences to guide social decision making (21,43) and tread carefully when their fate rests in our hands. Here, we provide evidence for an apparently hyperaltruistic valuation of others' pain that is associated with slower choices when making decisions that affect others.…”
Section: Discussionmentioning
confidence: 99%
“…Our experiments delineated AVP's role in mutually beneficial cooperation in an environment where altruistic concerns, reputation building, and strategically learning the partner's intentions and beliefs did not play a role (35,36). Most importantly, AVP did not change behavior in the social preferences control task, which rules out AVP working purely through increased altruistic one-sided prosociality.…”
Section: Discussionmentioning
confidence: 63%
“…However, previous work has shown that AVP administration increased cooperation following a cooperative gesture by one's partner in a repeated prisoner's dilemma (37), where cooperation might be mutually beneficial (38)-in line with the interdependent hypothesis (5). We believe that further investigation of AVP's role in social behavior would benefit from using computational theories that distinguish the different mechanism through which AVP may foster cooperative behavior in repeated interactions (35), particularly belief inference (33,36,39) and inferential limits in disorder (40).…”
Section: Discussionmentioning
confidence: 99%
“…It is argued that these two possible outcomes makes the game socially more interesting, than for example the prisoners dilemma, which has only one Nash equilibrium. The stag hunt allows for the study of cooperation within social structures (Skyrms 1996) and for studying the collaborative behavior of multi-agent systems (Yoshida et al 2008).…”
Section: Multi Agent Cooperative Game (Kl-stag-hunt)mentioning
confidence: 99%